Practicality of Contextual Learning Videos on Material Equality of Mass and Energy in Covid-19 Online Learning - Eka Susanti; Nelfi Erlinda; Lelfita Lelfita (Universitas PGRI Adi Buana Surabaya, 2022)
COVID-19 pandemic has changed many things in human life, including education where the learning process is now required to be online. Online learning has various drawbacks, one of which is the difficulty of students and lecturers connecting within the specified lecture time. Therefore, flexible and easily accessible learning media is needed to increase student understanding. Contextual learning videos are the solution that can answer these problems because of their flexibility and ease of access. The practicality of learning videos was evaluated through student responses to aspects of Ease of Use, Time Effectiveness, Attractiveness, and Benefits. The average score for the Ease of Use aspect is 86.24%, for the Time Effectiveness aspect it is 85.94%; the Attractiveness aspect scored 82.81%, and the Benefit aspect scored 85.42%. This study indicates that the learning video used was practical and very helpful in the online learning process during the Covid-19 period